Theory and Practice of the Public Sector Savings: The Case of Czech Regions - Milan PŮČEK; František OCHRANA (Transylvanian Review of Administrative Sciences, 2014)
In recent years, the necessity to allocate resources in economically rational ways has been amplified in the context of budget austerity measures and the overall tendency for balanced public budgets. Under these long-term circumstances, political leaders and public sector managers will be motivated to allocate available resources in economic, effective and purposeful ways, thus reducing waste of resources and seeking rational savings. The study shows some ways of achieving that goals by finding rational savings in the performance of delegated central government administration. The study analyzes expenditures and revenues for those tasks of central government administration that are delegated to regions in the Czech Republic. Based on the proposed theoretical concept of public sector savings and on the analysis of secondary and primary data, it assesses possibilities for achieving regional savings in delegated central government administration. Calculations based on empirical data demonstrate that regional governments have space for internal savings; benchmarking comparison and simulations confirm the possibilities for reducing waste of resources and achieving rational savings. Total calculated savings for all regions (for the year 2009) range between EUR 16 million and 29 million according to simulations, and the highest savings would be achieved by Central Bohemia.